Analysis of Implementation of Values of Bhineka Tunggal Ika in Elementary Schools - Adilatul Khairani; Ahmad Syachruroji; Siti Rokmanah (MANDALIKA : Journal of Social Science, 2023)
Parents are one of the main factors supporting the improvement of the quality of education in schools, especially with the presence of Covid-19, which requires students to study at home. Learning that is done at home certainly requires the help of parents. Because most students will often be at home when not supervised by their teacher. This certainly results in low application or implementation of Bhineka Tunggal Ika values ​​to students. This study aims to determine the implementation of the values ​​of Unity in Diversity in class IV SDN 28 Mataram. The research method used is qualitative with a descriptive approach. Data collection techniques using interviews, observation and documentation. While the data analysis technique in this study uses 4 stages including: data collection, data reduction, data presentation and conclusions. The results of the study show that in implementing the values ​​of Bhineka Tunggal Ika there are several activities used including the implementation of flag ceremony activities, IMTAQ activities and cultural Saturday activities. It can be concluded that the implementation of the values ​​of Unity in Diversity in class IV at SDN 28 Mataram has been carried out well, in which the implementation was implemented through several activities that existed before.